Maillard reaction intermediates in Chinese Baijiu and their effects on Maillard reaction related flavor compounds during aging - Hao Huang; Yuchen Gao; Lulu Wang; Xiaowei Yu; Shuang Chen; Yan Xu (Food Chemistry: X, 2024)
This study investigated the Maillard reaction in Baijiu and the effects of extended aging in the presence of Maillard reaction intermediates (MRIs) on aromatic compounds, particularly focusing on heterocyclic changes. MRIs with different aroma types in Baijiu aged 1–18 years and force-aged for 6 weeks were determined. Results revealed that MRIs in soy sauce aroma–type Baijiu were significantly more abundant than those in other types of Baijiu. Changes in MRIs were observed and compared in aging and forced-aging Baijiu. Additionally, the distribution and variation of heterocycles in Baijiu were examined, which revealed an increase in N-heterocycle levels but a decrease in S- and O-heterocycle levels to a certain extent. The results of this study demonstrate that the Maillard reaction during the aging of Baijiu influences heterocycle concentrations, thereby improving flavor of aged Baijiu. Research into heterocycles and the Maillard reaction may help elucidate the aromatic evolution of Baijiu with aging and provide guidance for Baijiu storage.